A REVIEW OF INDONESIAN INCLUSIVE EDUCATION RESEARCH IN ELEMENTARY SCHOOL : FROM 2015-2022 - Nuruddin; Muhamad Ahyar Rasidi; Hamzan (Walada: Journal of Primary Education, 2023)
This study utilizes a systematic literature review to (1) identify research subjects, (2) research subthemes, (c) research methodologies, and (d) research results in Indonesian primary schools. The PRISMA methodology was used to examine numerous literatures with similar topics in this study. The SINTA database is used for the article search. The PRISMA paradigm is implemented in four stages: identification, selection, classification, and inclusion. 37 papers were analyzed from these stages to get ready an overview of the findings. The study's findings show that the three primary themes that have emerged as the focus of inclusive research in Indonesia are the implementation of inclusive education, inclusive education policy, and the teaching and learning process in inclusive education. In general, the analysis of the literature shows that the implementation of inclusive education is proceeding as expected, with public schools beginning to accept the presence of children with disabilities in one moment of learning, with no discrimination against them by the teacher or the students themselves. However, the implementation of inclusive education is hampered by a shortage of competent human resources in dealing with children with special needs, therefore, instructors must be able to seek assistance and increase competency to enable better learning.